Stability Radii for Difference Equations with Time-varying Coefficients - Le, Hong Lan (H. : ĐHQGHN, 2017)
This paper deals with a formula of stability radii for an linear difference equation(LDEs for short) with the coeffecients varying in time under structured parameter perturbations. It is shown that the Ip- real and complex stability radii of these systems coincide and they are given by a formula of input-output operator. The result is considered as an discrete version of a previous result for time-varying ordinary differential equations.